PENERAPAN KEPEMIMPINAN PENDIDIKAN VISIONER DI SMK NEGERI 1 PURWOJATI - Rahmad Rismawan; Rochmat Cahyo Wibowo; Siswadi (STKIP Subang, 2026)
This study aims to describe the implementation of visionary educational leadership in managing educational financing at SMK Negeri 1 Purwojati. This research employed a qualitative approach, with data collected through interviews, observations, and documentation involving the principal, teachers, and students. Data were analyzed narratively to understand how visionary leadership is implemented in the context of educational financing management. The results indicate that visionary leadership at SMK Negeri 1 Purwojati is realized through the development of clear vision and mission statements, effective strategic planning, and strengthening the commitment of all school members. This implementation is reflected in program-based budgeting, collaboration with industry partners, and improving teacher competence through training programs. Additionally, transparency and accountability principles are applied in financial management. The implementation of visionary leadership has a positive impact on improving the quality of education, both in terms of teacher performance and student achievement. Therefore, visionary leadership is a crucial factor in supporting effective educational financing management and enhancing school quality. Keywords : Visionary leadership, educational financing, educational management, educational quality, vocational high school